Corpus et dictionnaires : prise de conscience linguistique chez des apprentis LANSAD - Landure, Corinne (My University, 2013)
Bilingual and monolingual dictionaries are mainly used by students as reference resources and are generally appreciated for their apparent simplicity of use and their efficiency, in particular concerning the immediacy of the results. Nevertheless, and maybe for these same reasons, they are very often underexploited by the users. With the democratization of innovative technologies, the consultation of corpora offers new possibilities and perspectives to second language learners. Numerous studies have shown the importance of corpus exploitation both at the level of the development of autonomy and of the linguistic awareness of the learners. Based on these reports, the present article describes a comparative study using a bilingual dictionary, a monolingual dictionary and a generic corpus to identify and understand certain items such as uncountable nouns in English. The experiment took place in a University Institute of Technology in France with the cooperation of students in the first year of Commercial Marketing. This work looks at the students' linguistic awareness according to the use of these three resources. The results of the study invite critical reflection on the means to be developed for effective practices of observation and intake of language by ESP learners.
Keywords: Data-driven learning; dictionaries; linguistic awareness; language events; corpus